Perancangan Sistem Pengelolaan Basis Data Peserta Pelatihan Widyaiswara pada Balai Diklat Keagamaan Provinsi Aceh - Safrizal Safrizal (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2019)
At the Aceh Provincial Education and Training Center, the widyaiswara training information service has not been optimally presented. Training data information in the form of training data, agenda, participants, alumni, and other data are still presented manually in printed form. During this time the form of documentation is only in the form of printed reports of activities, while the training data files are still shared by each activity committee. For the perfection of this research, the authors collected data using several data collection methods, including field studies and literature studies. Referring to the results of the author's research, designing the system in accordance with user needs as well as a variety of system tests and program tests in its design, in the end, the writer took several conclusions related to the analysis and management of the Widyaiswara training participant database at the Aceh Provincial Religious Education and Training Center which had been done, including that is, the system will greatly assist users or managers of widyaiswara training participants at the Aceh Provincial Education and Training Center more quickly, easily and accurately in all activities related to Widyaiswara training.